SARIDIN IN THE STRUGGLE BETWEEN ISLAM AND TRADITION: The Relevance of Islamism of Saridin for Character Education of Coastal Communities - Nur Said (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
This article is a research on the